A model for stealth coronal mass ejections. Issue 11 (5th November 2016) - Lynch, B. J.; Masson, S.; Li, Y.; DeVore, C. R.; Luhmann, J. G.; Antiochos, S. K.; Fisher, G. H.
Abstract: Stealth coronal mass ejections (CMEs) are events in which there are almost no observable signatures of the CME eruption in the low corona but often a well‐resolved slow flux rope CME observed in the coronagraph data. We present results from a three‐dimensional numerical magnetohydrodynamics (MHD) simulation of the 1–2 June 2008 slow streamer blowout CME that Robbrecht et al. (2009) called "the CME from nowhere." We model the global coronal structure using a 1.4 MK isothermal solar wind and a low‐order potential field source surface representation of the Carrington Rotation 2070 magnetogram synoptic map. The bipolar streamer belt arcade is energized by simple shearing flows applied in the vicinity of the helmet streamer's polarity inversion line. The flows are large scale and impart a shear typical of that expected from the differential rotation. The slow expansion of the energized helmet streamer arcade results in the formation of a radial current sheet. The subsequent onset of expansion‐induced flare reconnection initiates the stealth CME while gradually releasing the stored magnetic energy. We present favorable comparisons between our simulation results and the multiviewpoint SOHO‐LASCO (Large Angle and Spectrometric Coronagraph) and STEREO‐SECCHI (Sun Earth Connection Coronal and Heliospheric Investigation) coronagraph observations of the preeruption streamer structure and the initiation and evolution of the stealth streamer blowout CME. Key Points: Performed global MHD simulation of the 1‐2 June 2008 stealth coronal mass ejection observed by STEREO Large‐scale shearing of the bipolar helmet streamer arcade leads to expansion then slow CME eruption There is no real distinction between stealth CMEs and the lowest‐energy slow, streamer blowout CMEs